MEMERIKSA KEMBALI (LOOKING BACK) PEMECAHAN MASALAH MATEMATIS MENGGUNAKAN WEBSITE WOLFRAMALPHA PADA MATERI INTEGRAL TAK TENTU - Lukman Nurhakim; Badaruddin; Ahmad Yani T (CV. ADIBA AISHA AMIRA, 2023)
Mathematical problem solving can be done with four stages, namely understanding the problem, making a plan, executing a plan and looking back. The purpose of this paper is to describe the process of looking back at mathematical problem solving using the wolframalpha website. The results showed that re- examining can be done in various ways including asking teachers, asking friends who are mathematically higher or using technology. One technology that can be used as a tool to check back is the Wolframalpha application.